2001
DOI: 10.1136/bmj.323.7312.548
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetes in general practice: cross sectional population study

Abstract: Objective To assess the policy proposed by the American Diabetes Association of universal screening in general practice of all patients aged over 45 years for diabetes. Design Cross sectional population study. Setting Local general practice in the United Kingdom. Participants All patients aged over 45 not known to have diabetes. Main outcome measures Prevalence of diabetes in the screened population, cardiovascular risk profile of patients diagnosed as having diabetes after screening. Results Of 2481 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 11 publications
5
75
0
4
Order By: Relevance
“…On the other hand, the baseline predictors found in our study can easily be evaluated and used by physicians in treating patients in daily practice. It has been shown that screening for diabetes mellitus in general practice by measuring fasting blood glucose concentration is feasible, but has a very low yield in low risk population; 31 it could therefore be more beneficial in a high-risk patient group such as the present study population.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the baseline predictors found in our study can easily be evaluated and used by physicians in treating patients in daily practice. It has been shown that screening for diabetes mellitus in general practice by measuring fasting blood glucose concentration is feasible, but has a very low yield in low risk population; 31 it could therefore be more beneficial in a high-risk patient group such as the present study population.…”
Section: Discussionmentioning
confidence: 92%
“…In this section, studies that have assessed these costs and outcomes for different tests and test cut-off points are reviewed. 200 …”
Section: Studies Assessing the Costs And Short-term Outcomes Of Diabementioning
confidence: 99%
“…The overall compliance with a screening programme for type 2 diabetes is unknown. In this paper, sensitivity analyses with levels of compliance ranging from 30-75% were performed [8,9].The untreated risk model uses the risk prediction engine derived from the UK Prospective Diabetes Study (UKPDS), calculating the 5-year cumulative risk of CHD events (fatal or non-fatal myocardial infarction or sudden death) in people with diabetes (Table 1) [10]. The relative risk reduction for treatment of individual cardiovascular risk factors used in the risk reduction model are taken from a meta-analysis of single agent clinical trials in people with diabetes [11].…”
Section: Methodsmentioning
confidence: 99%